2004
DOI: 10.1128/mcb.24.9.3918-3927.2004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Hypoxia-Inducible Factor 1α-Responsive HGTD-P Gene as a Mediator in the Mitochondrial Apoptotic Pathway

Abstract: Hypoxia-inducible factor 1␣ (HIF-1␣) controls the cellular responses to hypoxia, activating transcription of a range of genes involved in adaptive processes such as increasing glycolysis and promoting angiogenesis. However, paradoxically, HIF-1␣ also participates in hypoxic cell death. Several gene products, such as BNip3, RTP801, and Noxa, were identified as HIF-1␣-responsive proapoptotic proteins, but the complicated hypoxic cell death pathways could not be completely explained by the few known genes. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
75
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 45 publications
4
75
0
Order By: Relevance
“…An up-regulation of the Bcl-xL expression occurred in the two cell types in correlation with the increase of the HIF-1α expression as well as a higher cell viability, while both cell types showed a down-regulation of Bcl-xL and an upregulation of Bax and cleaved-caspase-9 expression and an increase in the apoptotic index with the decrease of HIF-1α. These patterns were similar to that of the MKN-1 cells (15), supporting the correlation between the HIF-1α expression and apoptosis suggested by other reports (19,20).…”
Section: Discussionsupporting
confidence: 76%
“…An up-regulation of the Bcl-xL expression occurred in the two cell types in correlation with the increase of the HIF-1α expression as well as a higher cell viability, while both cell types showed a down-regulation of Bcl-xL and an upregulation of Bax and cleaved-caspase-9 expression and an increase in the apoptotic index with the decrease of HIF-1α. These patterns were similar to that of the MKN-1 cells (15), supporting the correlation between the HIF-1α expression and apoptosis suggested by other reports (19,20).…”
Section: Discussionsupporting
confidence: 76%
“…We have also shown that knockdown of endogenous BNIP3 in LS174T provides significant protection from hypoxically induced cell death. Less than 100% protection from hypoxic cell death in LS174T may be attributable to incomplete knockdown of the BNIP3 protein, or the result of hypoxic induction of other functional mediators of cell death of which several have been identified including Noxa and HGTD-P (Lee et al, 2004). Nonetheless, these functional data support the notion that hypoxic upregulation of BNIP3 in CRC cells significantly contributes to cell death.…”
Section: Discussionmentioning
confidence: 81%
“…HIF-1 is often considered to be essential for tumor growth and, indeed, its inhibition is the subject of ongoing drug development activities (44). However, under the appropriate conditions, HIF-1 activation can have negative consequences for tumor growth by induction of targets linked to apoptosis, such as BNIP3, E2IG5, PMAIP1, and DDIT4, or through metabolic alteration of cells in the low nutrient context of the tumor microenvironment (45).…”
Section: Discussionmentioning
confidence: 99%